2015
DOI: 10.1159/000365152
|View full text |Cite
|
Sign up to set email alerts
|

Children's Toothbrushing Frequency: The Influence of Parents' Rationale for Brushing, Habits and Family Routines

Abstract: Objectives: To assess the relationship between parental and family factors and children's toothbrushing frequency at different times of day. Methods: A cross-sectional questionnaire survey of predominantly low-socio-economic status parents of children aged 3-6 years (n = 296) in South Wales, UK. Data were collected on the child's weekly toothbrushing frequency (morning and evening), the parents' rationale for brushing their child's teeth in the morning and evening, the strength of a parent's habit for brushing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 27 publications
1
24
0
2
Order By: Relevance
“…Socioeconomic inequalities in adolescents' health have been documented previously . Family environment has been found to be strongly associated with children's tooth brushing . However, in our study, the family variable was not kept in the final logistical regression model.…”
Section: Discussionmentioning
confidence: 82%
“…Socioeconomic inequalities in adolescents' health have been documented previously . Family environment has been found to be strongly associated with children's tooth brushing . However, in our study, the family variable was not kept in the final logistical regression model.…”
Section: Discussionmentioning
confidence: 82%
“…This highlights the importance of these more modifiable volitional factors in future intervention programs and suggests past actions and habitual routines may be less stable across time. For example, parents may have different competing demands at different points in time that may potentially affect their ability to supervise their children's oral hygiene practices more or less (Trubey, Moore, & Chestnutt, ; Trubey et al ., ). It is important, therefore, for future interventions to improve parental behaviours for childhood oral hygiene to include elements of self‐efficacy, planning, and action control and link these with matched behaviour change techniques that have been shown to change the predictors, thus leading to interventions that may be optimally effective in changing behaviour (Kok et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The lack of effective results and cross‐over effect may be because young children's health behaviour is primarily directed by their parents, as children are unlikely to have the required capability and control over their own behaviours in the home (Cooper et al ., ; Hamilton, Cleary, White, & Hawkes, ). Considering dental decay is preventable (WHO, ) and children's heath is influenced by their parents behaviour (Hamilton, Spinks, White, Kavanagh, & Walsh, ; Hamilton, Cleary, et al ., ; Hamilton, Kirkpatrick, Rebar, White, & Hagger, 2017; Thomson, White, & Hamilton, ), including toothbrushing behaviours (Marshman et al ., ; Trubey, Moore, & Chestnutt, ), research is needed into the psychological processes that guide parents’ behaviour for their young children's toothbrushing behaviours to combat oral ill health in the early years (see Gray‐Burrows, Owen, & Day, ; Gray‐Burrows et al ., ). Indeed, a recent systematic review suggested a need for further prospective and experimental studies examining a range of psychological factors in relation to oral health behaviours (Scheerman et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Future analyses should explore which factors might contribute to these differences. Family conditions and social variables are key candidates for such analyses [45, 46].…”
Section: Discussionmentioning
confidence: 99%